Sistema informático de test on-line para la comisión de evaluación de la escuela superior politécnica agropecuaria de Manabí Manuel Félix López. - Adrián Heráclito, Alcívar Santander (2014)
In order to develop the computer system online assessments for the Evaluation Commission of Agricultural Polytechnic School of Manabí Manuel Felix Lopez, an analysis of assessment methods used by the accreditation committee for internal valuation was performed students. For efficient processing of the system and show that the results are supported technically worked with the methodology development process XP ( Extreme Programming ) which consists of four phases , within which was held from requirements gathering , with continuous collaboration evaluation committee which analyzed and classified the requirements and considerations that software must meet , completed this phase the design and adoption of a prototype was made in order to expedite and ensure that the user interface facilitates decision- evaluations later were programmed and validated components used in the system using Bootstrap to the visual environment and mode of interaction with the user, Entyti Framework, C # , JavaScript, Ajax and the paradigm of object-oriented to give functionality respectively programming , validating them by HTML5 , JavaScript and classes respectively, and thus enhance the development with the testing phase that ensured compliance with guidelines and characteristics considered in the initial development , the evidence allowed a 95% reduction in time to create , configure, and assign reagents to an evaluation , and 99% in the rating process and reports results.